Phytochemical Investigation and Simultaneously Study on Anticonvulsant, Antidiabetic Activity of Different Leafy Extracts of Bixa orellana Linn - Choudhury, G.B. (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The present study was carried out to investigate the anticonvulsant and antidiabetic activity of petroleum ether, ethyl acetate, diethyl ether, n-butanol and ethanol extracts of Bixa orellana Linn, leaves using experimental animal models. The extracts were screened for alkaloids, steroids, proteins, flavanoids, saponins, mucilage, carbohydrates, tannins, fats and oils. Anticonvulsant activity of above extracts was evaluated by using strychnine induced tonic convulsion of Swiss albino mice. All extracts were able to reduce convulsion in mice. The antidiabatic activity was evaluated in alloxan induced diabetic model of wistar rats. All the extracts were able to reduce sugar level in blood. Ethyl acetate and n-butanol extracts of this plant were found to have good antidiabetic activity in comparison to other extracts. The diethyl ether extracts of Bixa orellana was found to have good anticonvulsant activity in comparison to other extracts which was verified as statistically significant by using one way ANOVA at 1 % level of significance (p < 0.01).